Maitland Brown, a view of nineteenth century Western Australia - Cowan, Peter, 1914-2002. (Fremantle, W.A. : Fremantle Arts Centre Press, 1988)
Biography of western Australian politician, explorer, magistrate, farmer and merchant, Maitland Brown, one of the first generation of European setllers born in the Swan River colony; includes discussion of the Fairbairn report on the position of Aborigines and settlers in the Upper Murchison and Gascoyne.
Includes bibliographical references and index.
Keywords: Brown, Maitland, -- 1843-1905.; Explorers -- Western Australia -- Biography; Politicians -- Western Australia -- Biography; Farmers -- Western Australia -- Biography; Settlement and contacts - Colonisation - 1851-; History - Biographies - Non-Indigenous.; Government policy - State and territory - Western Australia; Western Australia -- History -- 1829-1900.; Western Australia (WA)